Nanoceria Prevents Glucose-Induced Protein Glycation in Eye Lens Cells - Belal I. Hanafy; Gareth W. V. Cave; Yvonne Barnett; Barbara K. Pierscionek (Nanomaterials, 2021)
Cerium oxide nanoparticles (nanoceria) are generally known for their recyclable antioxidative properties making them an appealing biomaterial for protecting against physiological and pathological age-related changes that are caused by reactive oxygen species (ROS). Cataract is one such pathology that has been associated with oxidation and glycation of the lens proteins (crystallins) leading to aggregation and opacification. A novel coated nanoceria formulation has been previously shown to enter the human lens epithelial cells (HLECs) and protect them from oxidative stress induced by hydrogen peroxide (H2O2). In this work, the mechanism of nanoceria uptake in HLECs is studied and multiple anti-cataractogenic properties are assessed in vitro. Our results show that the nanoceria provide multiple beneficial actions to delay cataract progression by (1) acting as a catalase mimetic in cells with inhibited catalase, (2) improving reduced to oxidised glutathione ratio (GSH/GSSG) in HLECs, and (3) inhibiting the non-enzymatic glucose-induced glycation of the chaperone lens protein α-crystallin. Given the multifactorial nature of cataract progression, the varied actions of nanoceria render them promising candidates for potential non-surgical therapeutic treatment.